ANALISIS PENGARUH INVESTASI TERHADAP PERKEMBANGAN INDUSTRI DI KOTA MEDAN - Lailan Safina Hasibuan, Sri Endang Rahayu (Jurnal Riset Akuntansi dan Bisnis, 2010)
Island Sumatera is one of the biggest island among thousand of island thoseare found in Indonesia, this island has an position strategic enough to be expanded.Specially North Sumatera that is Medan town. To look at the supporting condition, toprocess the natural wealth is necessary to be implicated soon to increase theprosperity of the citizenry and to raise territory so that it becomes a forward movingterritory. To process these resources a very big capital is needed, as very reliablepeaple or financial capital and skilled businessmen. Looking at the natural wealththat it possesses North Sumatera has a very great chance for investment that isdomestic investment and foreign investment because there are so many incompletematerials from various sectors. That’s why the province government specially Medantown always create an atmosphere that can stimulate investment, as local investmentalso foreign invetment.Problem statement of this research is : 1. What is the influence of thedomestic investment to the development of industry in Medan town?, and 2. What isthe influence of the foreign investment to the development of industry in Medantown? The purpose of this research is to know what is the influence of the domesticinvestment and foreign investment to the development of industry in Medan. Thesource of data in this research comes from secondary data in the form of yearlyreport that comes from official government or Medan Central Bereau Statistic,Planning and Development Province office, Investment and Promotion office.Technique analysis data use the econometrics model using ordinary least square(OLS).Based on the result of research, domestic investment has a positiveinfluence to the development industry of Medan with coefficient which means everyincrement 1% domestic investment, will cause the raise development industry inMedan as big as 0,001%. Also with the foreign investment has a positive influence todevelopment of industry in Medan as big as 0,001%. Determination coefficient showsthat as a whole domestic investment and foreign investment explain the influence oftheir relation with the development industry in Medan as big as 73,1% and the restso much as 26,9% is explained by other statistical variable that are not include in theestimation model.